Análisis de la eficiencia de la fertilización mediante el uso de Zeolita natural y Mucuna pruriens en el cultivo de arroz (Oryza sativa L.) bajo condiciones controladas en microparcelas situadas en Parrita, Puntarenas, Costa Rica (Repertorio Científico, 2020)
Analysis of the efficiency of fertilization through the use of natural Zeolite and Mucuna pruriens in the rice crop (Oryza sativa L.) under controlled environmental conditions in microplots located in Parrita, Puntarenas, Costa Rica. Objective: apply a source of green manure and zeolite in rice crop in order to see the possibility of improving fertilization efficiency and nutrient absortion. Method: Through at a dose of 152 g / m2 and a mineral source based on Zeolite with a dose of 38.25 g / m2, in different combinations with and without commercial fertilization in rice cultivation in Parrita, Puntarenas. Results: Regarding yield (ton/ha), the best treatment combined Zeolite + M.pruriens + commercial fertilization. Nitrogen absorption improved possibly due to Zeolite and M. pruriens for its qualities as physico-chemical conditioners and in the case of M.pruriens for its contribution of N. The C/N ratio, % of organic matter at ground level and content of K at leaf level, increased in all treatments, which was directly related to improving soil conditions.  Although the grain quality variable was not significant, it followed the same trend as yield. Conclusion: Despite not obtaining better yields than the national average, it was observed how the contribution of organic matter through conditioners and green fertilizers is significant and help improve soil conditions when applied.
Keywords: green manure; mucuna; zeolita; rice; nitrogen